(untitled) (Journal of Applied Oral Science, 2011)
Facial trauma can be considered one of the most serious aggressions found in the medical centers due to the emotional consequences and the possibility of deformity. In craniofacial surgery, the use of autologous bone is still the first choice for reconstructing bony defects or irregularities. When there is a shortage of donor bone or a patient refuses an intracranial operation, alloplastic materials such as polymethylmethacrylate (PMMA) can be used. The PMMA prosthesis can be pre-fabricated, bringing advantages such as reduction of surgical time, easy technical handling and good esthetic results. This paper describes the procedures for rehabilitating a patient with PMMA implants in the region of the face, recovering the facial contours and esthetics of the patient.